HYPERANDROGENISM AND VIRILIZING OVARIAN TUMOR (Fiep Bulletin - online, 2012)
The androgen-secreting ovarian tumors are relatively rare pathological conditions that happen with classic symptoms of hirsutism of sudden onset and rapid progression, as well as other important aspects of virilization. When it comes to rapid emergence of hyperandrogenic syndromes, always thinks of androgen-secreting ovarian tumors, although these conditions represent only 10% incidence in relation to other types of ovarian tumors. However, one cannot rule out other diseases that express your condition through increased production and/or biological activity of masculinizing hormones. Thus, signs of virilization are present when there is marked increase in the rate of production of testosterone which, in general, but not necessarily, be accompanied by corresponding increase in serum concentrations of the hormone. This pattern is characteristic of functioning tumors of the ovary and adrenal and ovarian hyperthecosis, but may also occur in the classic form of congenital adrenal hyperplasia. Through a case report were discussed the main features concerning the hyperandrogenic syndromes and hirsutism, highlighting key aspects of the diagnostic investigation, as well as the main differential diagnosis with special emphasis on the virilizing ovarian tumor.
Keywords: Hyperandrogenism; Hirsutism; Ovarian Neoplasms